Burger's medicinal chemistry and drug discovery : volume I: principles and practice - Burger, Alfred (New York : Wiley, 1995)
This updated edition covers the latest methods of drug discovery, as well as topics of current interest, such as computational chemistry and peptidomimetrics.
Information Sciences in Drug Discovery -- Drug Absorption, Distribution and Elimination -- Drug Biotransformations -- Drug Allergy --Structural Determinants of Carcinogenicity and Mutagenicity -- Molecular Recognition in Drug Design and Discovery -- Drug Receptors -- Drug-Target Binding Forces -- Chemical Information Computing Systems in Drug Discovery -- Quantitative Analysis of Structure-Activity Relationships -- Molecular Modelling in Drug Design -- Mass Ligand Screening in Drug Discovery -- Approach to the Rational Design of Enzyme Inhibitors -- Guidelines for Analog Design -- Natural Products as Leads for Pharmacueticals.
Keywords: PHARMACEUTICAL CHEMISTRY